Consequence Study of Hydrogen Release from Hydrogen Steam Reforming System - Muhammad Arif B Mohd Sazali, Muhammad Arif (Universiti Teknologi Petronas, 2011)
Many major accidents due to toxic release in the past have caused many fatalities such as the tragedy of MIC release in Bhopal, India. One of the approaches is to use consequence analysis study to minimize accidents and preparing for control mitigations. This technique is best implemented in preliminary design stage where the consequence of toxic release can be evaluated and necessary design improvements can be implemented to eliminate or minimize the accidents to as low as reasonably practicable (ALARP) without resorting to costly protective system. This paper reports on the preliminary findings on the development of consequence analysis and design improvement by utilizing an integrated process design simulator with consequence analysis model. The consequence analysis based on the worst-case scenarios during process flow sheeting stage was conducted as case studies. The preliminary finding shows that Phast DNV has capability to eliminate or minimize the potential toxic release accidents by adopting the inherent safety principle early in preliminary design stage.